2018
DOI: 10.2214/ajr.17.18817
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Image-Guided Spinal Lesion Biopsies: Factors Affecting Higher Diagnostic Yield

Abstract: For percutaneous image-guided biopsies of spinal tumorous lesions, diagnostic yield was 80%. Size, bone matrix, and final diagnosis of lesions affected diagnostic yield of percutaneous image-guided biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…There are many studies in the literature about percutaneous vertebral biopsies performed with the help of imaging. In a recent study by Yang et al [4], including 247 spinal tumor biopsies, the diagnostic success rate was 80%. This rate was 77% in the study of Wu et al [8] and 77.14% in the study of Puri et al [9].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There are many studies in the literature about percutaneous vertebral biopsies performed with the help of imaging. In a recent study by Yang et al [4], including 247 spinal tumor biopsies, the diagnostic success rate was 80%. This rate was 77% in the study of Wu et al [8] and 77.14% in the study of Puri et al [9].…”
Section: Discussionmentioning
confidence: 96%
“…This rate was 77% in the study of Wu et al [8] and 77.14% in the study of Puri et al [9]. The factors affecting diagnostic success were listed as size, bone matrix and definitive diagnosis of lesion in the study of Yang et al [4]. In the study of Gul et al [10], the success rate was found to be 80% and the only factor that had a significant relationship with success was reported as lesion histopathology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, they did not include cases of infectious spondylitis in their study. 23 In studies evaluating CT-guided biopsies specifically for vertebral osteomyelitis, the reported diagnostic yield has been much lower. For instance, Garg et al found histological examination provided positive results in 25 (41.0%) of the 61 samples collected for suspected cases of vertebral osteomyelitis; whereas the microbiology samples were even less predictive, with only 16 of the 84 samples collected (19.0%) yielding a positive result.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in imaging have improved lesion detection and also facilitated better differentiation of benign and malignant lesions. 1 In particular, Magnetic Resonance (MR) imaging, with its multiplanar capabilities, and excellent soft tissue contrast resolution, plays a pivotal role in characterizing these lesions. 2 Though some of these lesions (e.g., hemangiomas) have characteristic imaging findings, a definitive diagnosis is not always possible, and biopsy is needed to confirm the diagnosis of such indeterminate lesions.…”
Section: Introductionmentioning
confidence: 99%